PENGEMBANGAN BAHAN AJAR YANG BERORIENTASI PADA MODEL PEMBELAJARAN SOCIAL INQUIRY UNTUK MENINGKATKAN FINANCIAL LITERACY SISWA SEKOLAH DASAR - Aghni Khairunnisa, - (2021)
This research discusses the development of teaching materials to improve the financial literacy of elementary school students. It is important to note that this study presents the design of financial literacy teaching materials in which it uses the stages of social inquiry learning. This research is motivated by students' lack of understanding of financial literacy and the absence of financial literacy learning and supporting teaching materials at the elementary school level. This research aims to solve these problems by developing teaching materials to improve the financial literacy of elementary school students using a social inquiry learning model. The research method used is the R&D (Research and Development) research method developed by Robert Maribe Branch. The stages in conducting research consist of analyze, design, development, implementation, evaluation, abbreviated as ADDIE. The development of teaching materials begins with analyzing subjects, then made a teaching material structure which is then designed into a book to be tested for feasibility. The instruments used are tests, worklogs, interviews and expert validation. The research approach is carried out by processing the value of the questionnaire from experts and describing the advice and criticism given by experts to evaluate and improve the quality of teaching materials. Expert validation is done to media experts, material experts and teachers. Expert assessments are calculated using the Likert Scale to see the feasibility of the book. The result is an average percentage of expert validation that is, 90% with excellent categories. Teaching materials are also piloted to students through interviews and held pre-tests, post tests. Interview results showed students' positive responses to the book. The results showed an increase in pre-test and post- test results from an average of 52 to 82. From these results, books deserve to be used to improve the financial literacy of elementary school students.